2023
DOI: 10.1177/15394492221142597
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Facilitators to Telehealth Occupational Therapy for Autistic Children During COVID-19

Abstract: Pre-pandemic, telehealth occupational therapy (OT) for autistic children appeared promising, but research was limited. The pandemic provided a unique opportunity to investigate how clinics transitioned to telehealth. The purpose of this study was to examine barriers and facilitators that influenced delivery of OT services through telehealth for autistic children during the pandemic. We conducted semi-structured qualitative interviews with 13 participants (three administrators, six OTs, and four parents of auti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…As most occupational therapists are considered novice in the practice of telehealth in the Philippines, the PAOT has created a set of guidelines (Philippine Academy of Occupational Therapists, 2020) to ensure that the quality of services provided in telehealth is the same as occupational therapy services delivered in-person, complying with all jurisdictional, institutional, and professional regulations (World Federation of Occupational Therapists, 2021). Recently, a summary of reported strategies for promoting successful telehealth occupational therapy sessions is available with the following overarching phases: 1) staff trainings on telehealth occupational therapy; 2) resources for families and staff; 3) interventions and in-session strategies; and 4) parent education and coaching (Angell et al, 2023).…”
Section: Telehealth: An Alternative or A Strategic Tool In Occupation...mentioning
confidence: 99%
See 2 more Smart Citations
“…As most occupational therapists are considered novice in the practice of telehealth in the Philippines, the PAOT has created a set of guidelines (Philippine Academy of Occupational Therapists, 2020) to ensure that the quality of services provided in telehealth is the same as occupational therapy services delivered in-person, complying with all jurisdictional, institutional, and professional regulations (World Federation of Occupational Therapists, 2021). Recently, a summary of reported strategies for promoting successful telehealth occupational therapy sessions is available with the following overarching phases: 1) staff trainings on telehealth occupational therapy; 2) resources for families and staff; 3) interventions and in-session strategies; and 4) parent education and coaching (Angell et al, 2023).…”
Section: Telehealth: An Alternative or A Strategic Tool In Occupation...mentioning
confidence: 99%
“…Moreover, while providing occupational therapy services, Filipino occupational therapists, at that time, were encouraged to attend training that is specific on telehealth provision provided by local and international professional organizations to augment their lack of training in telehealth (Sy et al, 2020). Although the steps were not exactly akin to Angell's et al (2023) list of telehealth strategies, it is evident that telehealth procedures are still evolving and changing the occupational therapy practice landscape to date. We, however, need to reflect and act upon the issue about how telehealth, as a tool, can be maximized in resource-constrained countries juxtaposing varying contexts and dimensions including family values, a health system that is not oriented towards primary care and has a low recognition of occupational therapy as a profession.…”
Section: Telehealth: An Alternative or A Strategic Tool In Occupation...mentioning
confidence: 99%
See 1 more Smart Citation
“…An OTJR: Occupational Therapy Journal of Research special issue on telehealth similarly noted that telehealth went from an ‘emerging’ delivery model to defining everyday practice during COVID-19 ( Little & Proffitt, 2023 ). Studies included within this special issue broadly concluded that telehealth-delivered occupational therapy presents both advantages and limitations across varying practice settings and populations ( Angell et al, 2023 ; Lamash et al, 2023 ; Little et al, 2023 ; Pineda et al, 2023 ; Sleight et al, 2023 ). Participants from these studies often supported ongoing telehealth-delivered occupational therapy, but not necessarily as a universal replacement for in-person care ( Angell et al, 2023 ; Pineda et al, 2023 ).…”
mentioning
confidence: 99%
“…Telehealth can require parents of CSHCN to directly support their child technologically, physically, and contextually based on session implementation goals. Being hands-on, while parents are also caring for potential siblings, home, and work obligations, potentially increases parental stress and feelings of responsibility during telehealth when compared with an in-person visit (Angell et al, 2023; Camden & Silva, 2021). Pediatric rehabilitation providers also report telehealth barriers including feeling limited in provider evaluation and intervention options without hands on capacities, and experiencing a steep implementation learning curve often without formal training availability (Wittmeier et al, 2022).…”
mentioning
confidence: 99%